The Legal Responsibilities of Officials Making Land Deeds against the Crime of Forgery of Sale and Purchase Deeds - Kinanthi, Lembah Nurani Anjar; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This study aims to identify and analyze the legal responsibility of land deed drafting officials for the crime of sale and purchase deed forgery. This study uses a normative juridical approach (normative legal research method), uses a Statute Approach and a Case Approach. The type and source of data that researchers use is secondary data, divided into primary legal materials, secondary law as well as tertiary law. The data collection method uses document study or literature study and the data analysis method uses qualitative methods. Based on the research, it was concluded that the legal responsibility of the official making the land deed who committed the criminal act of falsifying the sale and purchase deed in Decision No. 248/Pid.B/2022/Pn.Jkt.Brt., states that if the defendant F, SH.MKn and the defendant IR, SH, with imprisonment for two years and eight months each, a fine of IDR 1,000,000,000 each. The deed of sale and purchase as well as the full power of attorney made by the two PPATs are truly inauthentic or contain defects, so that the position of the deed of sale and purchase as an authentic deed can be canceled and the status of the sale and purchase agreement is degraded to an underhanded agreement. Meanwhile, the responsibility of the official making the land deed as a general official for inauthentic sales and purchase deeds, namely administrative responsibility, civil responsibility and criminal responsibility. Keywords: Accountability; Land; Purchase.